Tutorial on Kelly capital growth investment strategies for long term growth with application to SWFs 2 - Ziemba, William (Henry Stewart Talks, 2014)
Samuelson’s critique of Kelly betting, Fractional Kelly and negative power utility, Some tests, Commodity trading: turn of year effect, Lotto games, experimental data, Calculating the optimal Kelly fraction, Extension in MacLean, Zhao, Ziemba (2009) paper, Asset prices, Regimes, Wealth dynamics, Capital growth with penalty, Optimal growth, Decomposition, One period problem, Functional form, Wealth trajectories